Cross-reactive dengue human monoclonal antibody prevents severe pathologies and death from Zika virus infections - Kam, Yiu-Wing (2018)
Zika virus (ZIKV) infections have been linked with neurological complications and congenital Zika syndrome. Given the high level of homology between ZIKV and the related flavivirus dengue virus (DENV), we investigated the level of cross-reactivity with ZIKV using a panel of DENV human mAbs. A majority of the mAbs showed binding to ZIKV virions, with several exhibiting neutralizing capacities against ZIKV in vitro. Three of the best ZIKV-neutralizing mAbs were found to recognize diverse epitopes on the envelope (E) glycoprotein: the highly conserved fusion-loop peptide, a conformation-specific epitope on the E monomer, and a quaternary epitope on the virion surface. The most potent ZIKV-neutralizing mAb (SIgN-3C) was assessed in 2 type I interferon receptor–deficient (IFNAR–/–) mouse models of ZIKV infection. Treatment of adult nonpregnant mice with SIgN-3C rescued mice from virus-induced weight loss and mortality. The SIgN-3C variant with Leu-to-Ala mutations in the Fc region (SIgN-3C-LALA) did not induce antibody-dependent enhancement (ADE) in vitro but provided similar levels of protection in vivo. In pregnant ZIKV-infected IFNAR–/– mice, treatment with SIgN-3C or SIgN-3C-LALA significantly reduced viral load in the fetal organs and placenta and abrogated virus-induced fetal growth retardation. Therefore, SIgN-3C-LALA holds promise as a ZIKV prophylactic and therapeutic agent.